Use of Iron Oxyhydroxides as Water Decontaminants: the Case of Akaganeite (2022)
ABSTRACT: Humanity recognizes the vital importance of adequate access to safe drinking water for a population that is growing in number. However, various human activities along with climate change can lead to an increase in contaminated water. Therefore, the minimization of the content of water contaminants has long been the subject of worldwide research. Within the various methods that exist to remove contaminants in aqueous media, there is the use of adsorbents based on iron oxides and oxyhydroxides. In this sense, the most commonly used samples for adsorption are ferrihydrite, goethite, feroxyhyte, hematite, and magnetite. Comparatively, akageneite has been less employed, in spite their unique properties for the efficient removal of water pollutants [1]. In this work, we review our contributions to both: (i) the synthesis of pure and co-precipitated akaganeites in presence of different cations such as aluminium, chromium, copper, mercury, antimony and arsenic, and also (ii) the study of the adsorption kinetics of mercury, antimony, and arsenic onto some modified akageneite nanoparticles [2]. We reported that: (i) it seems that the investigated cations did not replace iron in their crystallographic sites, (ii) some cations produced important particle size reductions and changes in the Mössbauer parameters, and (iii) the nanosized akaganeites had much better adsorption capacities than pure akaganeites. Finally, many adsorptions kinetic models have been reported in the literature, but only very few of them have been used to fit the kinetic experimental data. It is important to know the kinetic characteristics, because it allows a prediction of the rate of removal of contaminants using adsorbents, which is a crucial factor for the design and operation of an effective adsorption system. In this work, 22 models have been explored and it was found that the fractal kinetic models were the ones that better described the kinetic adsorption processes. References: [1] E.A. Deliyanni, G.Z. Kyzas, K.A. Matis. Composite Nanoadsorbents 337 (2019) https://doi.org/10.1016/B978-0-12-814132-8.00015-0 [2] V. Villacorta, C.A. Barrero, M.B. Turrión, F. Lafuente, J.-M. Greneche and K.E. García. RSC Advances 10, 42688 (2020). DOI: https://doi.org/10.1039/d0ra08075f.